Mesenchymal Stem/Stromal Cells in Progressive Fibrogenic Involvement and Anti-Fibrosis Therapeutic Properties - Li, Chenghai; Wang, Bin (Frontiers in Cell and Developmental Biology, 2022)
Fibrosis refers to the connective tissue deposition and stiffness usually as a result of injury. Fibrosis tissue-resident mesenchymal cells, including fibroblasts, myofibroblast, smooth muscle cells, and mesenchymal stem/stromal cells (MSCs), are major players in fibrogenic processes under certain contexts. Acknowledging differentiation potential of MSCs to the aforementioned other types of mesenchymal cell lineages is essential for better understanding of MSCs’ substantial contributions to progressive fibrogenesis. MSCs may represent a potential therapeutic option for fibrosis resolution owing to their unique pleiotropic functions and therapeutic properties. Currently, clinical trial efforts using MSCs and MSC-based products are underway but clinical data collected by the early phase trials are insufficient to offer better support for the MSC-based anti-fibrotic therapies. Given that MSCs are involved in the coagulation through releasing tissue factor, MSCs can retain procoagulant activity to be associated with fibrogenic disease development. Therefore, MSCs’ functional benefits in translational applications need to be carefully balanced with their potential risks.